Synthesis of sulfonated poly(diketonephenylene)s containing dibenzoyl moiety via Ni/Zn catalyst. (19th January 2017) - Yoo, Jiho; Jang, Hohyoun; Sutradhar, Sabuj Chandra; Ha, Jaeseong; Choi, Kunyoun; Ryu, Taewook; Yang, Hanmo; Yoon, Sujin; Kim, Whangi
Abstract: The new monomer, 1, 2-bis(4-chlorobenzoyl)-3, 6-diphenylbenzene, was synthesized from the Frieldel–Craft reaction of chlorobenzene and fumaryl chloride followed by the Diels–Alder reaction. Poly(diketonephenylene)s containing the dibenzoyl moiety in the side chains were synthesized from 1, 2-bis(4-chlorobenzoyl)-3, 6-diphenylbenzene and 1, 4-dichloro-2, 5-dibenzoylbenzene as a reactive monomer. The polymerization was performed employing a Ni/Zn catalyzed carbon–carbon coupling reaction followed by a sulfonation reaction with chlorosulfuric acid. These polymers consisted of diketone in the main chain and dibenzoyl in the side chain, which consisted of four active phenyl groups for sulfonation. A series of membranes was studied via 1 H NMR spectroscopy, ion exchange capacity (IEC), water uptake, and proton conductivity analyses. The thermal and chemical stability of the prepared membrane is then characterized through a thermogravimetric investigation. Graphical abstract: A series of SPTBP were synthesized via Suzuki coupling reaction using nickel/phosphine/zinc catalyst with 1, 2-bis(4-chlorobenzoyl)-3, 6-diphenylbenzene and 2, 5-dichloro-1, 4-dibenzoylbenzne. The polymer had molecular weight (Mw ) from 110, 500 to 124, 200. Compared with Nafion 211 ® membrane, these membranes showed IECs from 1.15 to 2.28 meq./g, water uptake from 10.19 to 61.22%, proton conductivity from 61.2 to 110.2 mS/cm, and high thermal stability. The clear microphase separation and inhomogeneity structured membranes had much higher proton conductivities, even higher than Nafion at high IEC values. Highlights: A series of the sulfonated poly(diketonephenylene) were synthesized. The degree of sulfonation was controlled by chlorosulfuric acid. Increasing sulfonation level increases proton conductivity. Membranes have good performances with high dimensional stability.